Hypervolemic Hemodilution as a Management During Predicted Massive Bleeding Sectio Caesarea in Placenta Accreta Patient - Fanniyah Fanniyah; Ruddi Hartono (Faculty of Medicine, Brawijaya University, 2022)
Background: Placenta accreta represent one of the most morbidity condition in modern obstetrics, with high rates of hemorrhage, hysterectomy and intensive care unit admission. Alternative management during intraoperative bleeding is haemodilution. There are two techniques in hemodilution, autonomic normovolemic hemodilution (ANH) and hypervolemic hemodilution.Case: A gravida patient with ASA 2 physical status with a suspected placenta accreta was planned for a sectio caesarea. To anticipate bleeding, hypervolemic hemodilution was conducted. Hemodilution was performed with a total fluid of 2000cc. Total bleeding during surgery is 3500 cc. A close monitoring of haemoglobin (Hb) and haematocrit (Hct) was conducted. The initial Hb and Hct were 9.9 mg/dl and 29.8%, respectively. The Hb and Hct results post-haemodilution were 5.7 and 17.1, respectively. The postoperative Hb and Hct results were 5.4 mg/dl and 16.6%, respectively. The patient was given a blood transfusion of 450 cc PRC (packed red cells).. The patient was observed in the ICU for 24 hours postoperatively and was subsequently transferred to the ward. Hemodilution, in this case, was proven to be effective based on the post-hemodilution and post-haemorrhage Hb and Hct results. The total bleeding was 3500 cc, and there was a reduction of Hb from 5.7 to 5.4 and haematocrit from 17.7% to 16.6%. Conclusion: Due to the hemodilution, not only the red blood cells were lost, but also the hemodilution fluids. Hemodilution may be an alternative management during intraoperative haemorrhage. However, the anticipation and effect that might arise from hemodilution should be considered. Keywords: Accreta, Hemodilution, Hypervolemic hemodilution, massive hemorrhage.